Limiting extracellular matrix expansion in diet-induced obese mice reduces cardiac insulin resistance and prevents myocardial remodelling - Vishal Musale; Colin E. Murdoch; Ayman K. Banah; Annie Hasib; Chandani K. Hennayake; Bo Dong; Chim C. Lang; David H. Wasserman; Li Kang (Elsevier, 2024)
Objective: Obesity increases deposition of extracellular matrix (ECM) components of cardiac tissue. Since obesity aggregates with insulin resistance and heart disease, it is imperative to determine whether the increased ECM deposition contributes to this disease cluster. The hypotheses tested in this study were that in cardiac tissue of obese mice i) increased deposition of ECM components (collagens and hyaluronan) contributes to cardiac insulin resistance and that a reduction in these components improves cardiac insulin action and ii) reducing excess collagens and hyaluronan mitigates obesity-associated cardiac dysfunction. Methods: Genetic and pharmacological approaches that manipulated collagen and hyaluronan contents were employed in obese C57BL/6 mice fed a high fat (HF) diet. Cardiac insulin sensitivity was measured by hyperinsulinemic-euglycemic clamp and cardiac function was measured by pressure-volume loop analysis in vivo. Results: We demonstrated a tight association between increased ECM deposition with cardiac insulin resistance. Increased collagen deposition by genetic deletion of matrix metalloproteinase 9 (MMP9) exacerbated cardiac insulin resistance and pirfenidone, a clinically available anti-fibrotic medication which inhibits collagen expression, improved cardiac insulin resistance in obese mice. Furthermore, decreased hyaluronan deposition by treatment with PEGylated human recombinant hyaluronidase PH20 (PEGPH20) improved cardiac insulin resistance in obese mice. These relationships corresponded to functional changes in the heart. Both PEGPH20 and pirfenidone treatment in obese mice ameliorated HF diet-induced abnormal myocardial remodelling. Conclusion: Our results provide important new insights into the role of ECM deposition in the pathogenesis of cardiac insulin resistance and associated dysfunction in obesity of distinct mouse models. These findings support the novel therapeutic potential of targeting early cardiac ECM abnormalities in the prevention and treatment of obesity-related cardiovascular complications.